Operating Room Biodegradable Instrument Use Attitudes of the Surgical Team - Abduleilah yahya abumaghayed ,Fayez Alshammari ,Faris alanazi ,Fahad Alshammari,Bassam alshammari ,Ammash alshammari ,Khalil Alshammari ,Abdullah Alreshidi ,manal alrashidy ,Amal alrashidi ,khalid alreshidi ,Maha Alsuhaimi ,Mamdouh Nafel Alrshidi; Ashraf Baboor ,Rozan Radwan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
The healthcare sector generates considerable volumes of trash, most notably in operating rooms (ORs), which aggravates global environmental damage.  The aim of this study was to assess recycling policies used in different surgical disciplines worldwide in operating rooms, therefore pointing up significant challenges and areas for development.  Governmental constraints, inadequate knowledge, poor leadership, and organizational problems are among the several elements that complicate the implementation of recycling ideas.